If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 = 13u Solving -2 = 13u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-13u' to each side of the equation. -2 + -13u = 13u + -13u Combine like terms: 13u + -13u = 0 -2 + -13u = 0 Add '2' to each side of the equation. -2 + 2 + -13u = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -13u = 0 + 2 -13u = 0 + 2 Combine like terms: 0 + 2 = 2 -13u = 2 Divide each side by '-13'. u = -0.1538461538 Simplifying u = -0.1538461538
| -3x-2y=-8 | | 3+7c=2c-3 | | 4+3r-4r=4 | | 10x^2-3x-23=4 | | -8n+5n=-12 | | 5x*x=25 | | x+3-4x=-18 | | 2x^2-1.2x-1.6=0 | | 5-6x=2x+5 | | 0=4-7n-4 | | 13+a/4=-3 | | (2x-5)(3x+7)=0 | | -4(-5-7n)-4=-96 | | -2x+1=3(x-8) | | -663x^4-7x^3= | | X+4x=70 | | 10ln(n)n=2 | | -8(2+8x)=-400 | | 9x+4x=20 | | 1x+3=2(x-4) | | 12(5-1)-4(2s-1)=2(s+1) | | 1=1+6x-8x | | 5n^2+27n=18 | | 5n^2+27n=28 | | 17=2m+8-5m | | (16x-5)/10=x/5 | | 6=n/4+2 | | 16x-5/10=x/5 | | 4x+1y=1.73 | | -9x=-3(x-4) | | 7b-b+2a= | | 12r-25=4r+7 |